STUDY ON DOPPLER EFFECT BASED ON FREQUENCY AND VELOCITY OF SOUND SOURCE IN THE WATERS - Husni, Iqbal Ali; Akbari, Hafsarizka; Hidayat, Rizqi Rizaldi; Hartoyo, Hartoyo; Amron, Amron (Prodi Fisika FST UNJA, 2024)
The Doppler effect is an important factor in studying marine resources using hydroacoustic technology. Several factors that influence the Doppler effect in waters are the frequency and velocity of the sound source. This research aimed to study the characteristics of sound received based on the frequency and velocity of the sound source as a representation of the Doppler effect. The research was designed using 5 lines as a variation in frequency (1000 and 5000 Hz) and velocity of sound source. The result showed that the Doppler effect was determined by changes in frequency, but was not significantly measured by changes in sound intensity. The frequency of the sound was increased as the frequency of the sound source increased. The receiver frequency also be higher if the angle between the receiver and the sound source was smaller or if the sound source was further away from the receiver.